THE INDIAN GURU-SISHYA TRADITION: A MODEL FOR TOMORROW : . - Palatty, Paul (Journal of Dharma, 2002)
The master-disciple relationship is a phenomenon common to all religions and their mystical traditions. It can be regarded as the most uni versal and the most particular dyad I. A closer look may reveal that the figure of the Master and that of the disciple are interdependent and inseparable archetypes/. "A disciple is born when a true master is found, it is in turn the surrender of the disciple which makes the master’." In any ultimate religious experience, a radical self-surrender is seen as the indispensable condition", The Master enables the disciple to express the surrender and the disciple becomes conscious of the surrender to a master. This is the core of the master-discipleship relationship